Pengaruh Keahlian Komite Audit Dan Ukuran Komite Audit Terhadap Kualitas Pelaporan Keuangan di Sektor Infrastruktur - Diki Wahyudi; Rahman Anshari; Muhammad Iqbal Pribadi (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2025)
Companies operating in the infrastructure industry will be the focus of this research, which seeks to determine how audit committee size and competence affect the reliability of financial reports. The reliability and accuracy of a company's financial reports is an important indicator of its honesty and responsibility. An important aspect of good corporate governance is the audit committee's responsibility to monitor the accuracy of financial reports. Participants in the research are infrastructure companies that will be listed on the IDX in the years 2020–2023. The purposive sampling strategy was used to choose a sample of 112 data points for examination in research using multiple linear regression using SPSS. While the research found that audit committee expertise much reduces financial reporting quality, it found that audit committee size greatly improves it.